Inclusion and Trace Elements in Quartz LA-ICP-MS Analysis and Research - Wang, Rongrong (International Journal of Natural Resources and Environmental Studies, 2025)
This article conducts quartz inclusion and trace element testing and analysis on quartzite in a certain area of Henan Province, and preliminarily determines the occurrence state of impurity elements inside the quartzite. The main impurity elements are mainly associated minerals, inclusions, and lattice impurities that exist inside the quartz. By observing the mineral composition inside quartzite under a microscope, the type of impurity minerals can be preliminarily determined; In situ determination of the composition of gas-liquid inclusions inside quartz using a high-resolution confocal laser Raman spectroscopy imaging system; By using a laser ablation inductively coupled plasma mass spectrometer, the trace element composition of quartz is determined to determine the content and occurrence state of impurity elements.